2006
DOI: 10.1063/1.2357553
|View full text |Cite
|
Sign up to set email alerts
|

Parametric modulation of an atomic magnetometer

Abstract: The authors report on a rubidium atomic magnetometer designed for use in a shielded environment. Operating in the spin-exchange relaxation-free regime, the magnetometer utilizes parametric modulation of the z-magnetic field to suppress noise associated with airflow through the oven and to simultaneously detect x- and y-field components, using a single probe beam, with minimal loss of sensitivity and bandwidth. A white noise level of 60 fT/(Hz)(1/2) was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 10 publications
0
57
0
Order By: Relevance
“…In practical situations, significant 1/f noise may arise due to external elements, such as laser fluctuations caused by air currents. Such noise may be reduced using spin modulation techniques [47].…”
Section: Additional Characteristics Of a Magnetometermentioning
confidence: 99%
“…In practical situations, significant 1/f noise may arise due to external elements, such as laser fluctuations caused by air currents. Such noise may be reduced using spin modulation techniques [47].…”
Section: Additional Characteristics Of a Magnetometermentioning
confidence: 99%
“…When the field parallel to the pump beam B z corresponds to a Larmor frequency greater than the atomic relaxation rate, the magnetometer also has a significant resonant response to the field B x parallel to the probe beam; the response in this regime is comparable in magnitude to the response to B y . 8 Thus, the measured noise spectrum V m (f ) is composed of the magnetometer response to noise in both x and y directions and can be calibrated using…”
mentioning
confidence: 99%
“…This limits the sensitivity of the SERF magnetometer at the lower frequency. Li et al previously demonstrated a SERF magnetometer using parametric modulation to suppress nonmagnetic technical noise, but laser intensity fluctuation was not suppressed [14]. To date, a SERF magnetometer suppressing laser intensity noise and thermal noise simultaneously has not been reported.…”
Section: Introductionmentioning
confidence: 97%